Measuring Deeper Learning Through Cognitively Demanding Test Items Results from the Analysis of Six National and International Exams - Yuan, Kun (RAND Corporation, 2014)
Two test consortia are developing a next generation of tests to measure students' attainment of the Common Core State Standards. These tests are expected to assess greater deeper learning skills than existing large-scale tests. A RAND study rated the cognitive demand of six nationally and internationally administered exams. The findings establish a benchmark for comparing how well the new generation of tests performs in assessing deeper learning.